Intention to Use Contraceptive Methods among Women Undergoing Comprehensive Abortion Care (Cac) in Maternity Hospital Kathmandu, Nepal - Shrestha, Rubina; Taechaboonsermsak, Pimsurang; Siri, Sulkontha (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Unplanned and unwanted pregnancy is one of the leading causes of maternal mortality and morbidity and still continues despite availability of a range of modern and effective contraceptives. Comprehensive Abortion Care (CAC) is to provide safe, high quality services to women in an affordable and acceptable way. The study is intended to identify the proportion of the women who have intention to use contraceptive methods following CAC, in the future and to know the reason for current nonuse. MATERIAL AND METHODS: A descriptive cross-sectional study of women undergoing CAC in maternity hospital Kathmandu was conducted from 1st February to 21st February 2011. Different factors affecting Intention to use contraceptives following CAC and their association were identified and analyzed. SPSS statistical software was used to perform analysis. RESULTS: Following CAC 61.5% had an intention to use contraceptives, injectables being the most common method followed by IUCD and pills. Side effects were the main reason for stopping and not having an intention to use. There was a significant association between duration of marriage,current use of contraceptive methods, attitude towards contraceptive method, subjective norm and intention to use contraceptive methods. CONCLUSION: The acceptance of contraceptives can be increased by having positive attitude, providing sufficient information to avoid fear related to side effects. Journal of Universal College of Medical Sciences (2016) Vol.04 No.02 Issue 14, page: 10-13